Effect of perinatal biotin deficiency on auditory pathway of the Wistar-Albino rats. (3rd August 2019) - Yılmaz, Nevreste Didem Sonbay; Gür, Özer Erdem; Ensari, Nuray; Bulut, Erdogan; Kaya, Ozlem Tugce; Sırvancı, Serap; Danısman, Betul; Derin, Narin; Gezgin, Bahri; Aygener, Nurdan; Yılmaz, Mustafa Deniz
Abstract: Aim: Severe biotin deficiency associated with biotinidase enzyme deficiency in newborns is seen as severe neurological problems and hearing loss. However, the effect on the infant of deficiencies in the maternal diet during pregnancy are not clear. Material and methods: The study included 16 female Wistar albino rats and 4 male Wistar albino rats, that were mated and then the females were separated into 4 groups. At 40 days after the birth, 3 pups were selected from each group, and these 12 pups were evaluated with DPOAE and ABR electrophysiologically and the cochlea was examined ultrastructurally with electron microscopy. Results: In the DPOAE evaluation, At 8000 and 11, 000 Hz, the signal-noise ratios in the B-N and B-B groups were statistically significantly higher ( p < .05). In ABR, lengthening of the latency periods was determined in all the waves at both 8 and 16 kHz in the B-B group. When the IPL periods were examined, lengthening in IPL 1–5 was statistically significant in the B-B group only at 8 kHz. Conclusions: Biotin can be said to have an effect on hearing pathways. However, specifically where on the hearing pathways that biotin is involved has not been clarified.